2015
DOI: 10.1056/nejmsa1413299
|View full text |Cite
|
Sign up to set email alerts
|

Appointment Availability after Increases in Medicaid Payments for Primary Care

Abstract: Our study provides early evidence that increased Medicaid reimbursement to primary care providers, as mandated in the ACA, was associated with improved appointment availability for Medicaid enrollees among participating providers without generating longer waiting times. (Funded by the Robert Wood Johnson Foundation.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 227 publications
(188 citation statements)
references
References 8 publications
9
179
0
Order By: Relevance
“…8 This could be due to low Medicaid reimbursement rates in the area which are less than one-third of private rates, as research shows that increasing Medicaid reimbursement increases availability of appointments for Medicaid patients. 27 Texas is choosing not to expand Medicaid under the Affordable Care Act, and our study suggests that expansion of Medicaid may not help patients gain access to outpatient orthopedic care in the state, at least not at current Medicaid physician rates.…”
Section: Discussionmentioning
confidence: 74%
“…8 This could be due to low Medicaid reimbursement rates in the area which are less than one-third of private rates, as research shows that increasing Medicaid reimbursement increases availability of appointments for Medicaid patients. 27 Texas is choosing not to expand Medicaid under the Affordable Care Act, and our study suggests that expansion of Medicaid may not help patients gain access to outpatient orthopedic care in the state, at least not at current Medicaid physician rates.…”
Section: Discussionmentioning
confidence: 74%
“…Many rural and inner-city areas lack adequate health care. Some physician practices do not accept Medicaid insurance (112). Many US hospital systems operate dual systems of care: care by faculty for private patients and care by residents for those on Medicaid and those with no insurance (8,114).…”
Section: Principle 3 Social Disadvantage Is Associated With Worse Hementioning
confidence: 99%
“…One study by Polsky et al (2015) used a "secret shopper" methodology to assess changes in appointment availability in ten states before and after implementation of the payment increase. The analysis by Polsky et al showed that appointment availability for Medicaid patients increased by 7.7 percentage points after the payment increase, while there was no simultaneous increase for privately insured patients.…”
Section: Prior Research Examining the Impact Of The Policymentioning
confidence: 99%